Community Development by Employing Photovoltaic Solar Sewing - Ernst August Uken (Journal of Basic & Applied Sciences, 2020)
A person's culture must be respected before embarking on mass roll-outs of a new innovation. The pedestal of culture rests on the following often non-negotiable legs: language, norms, values, beliefs, roles and social collectives. These are briefly explained before reporting on the experiences of various parties intending to roll out their innovation towards the social development of communities. Examples of failures are cited like smokeless stoves where the community was not consulted beforehand. Similar failures were reported with the solar cookers from Europe. Subsequent interviews revealed practical reasons for the non-acceptance by the local community. The approach of marrying culture and technology beforehand is thus emphasised. A classic example is to be found with the successful conceptualisation, development and commissioning of a patented 12v DC solar photovoltaic sewing machine. It was deployed in a remote, rural area of the North-Western Cape of South Africa. The world's first solar sewing station, earning money for unemployed housewives was developed at Kliprand thanks to the financial support of USAID and the South African Foundation for Research Development (FRD). Before launching a development project one needs to ask: Why is my innovation viable? When is it viable? How viable is it now and in future? Where is it competitive? The Conclusion of this paper will therefore almost serve as a guideline for well-meaning developers for Africa and beyond